A comparison of clearfelling and gradual thinning of plantations for the restoration of insect herbivores and woodland plants. Issue 6 (26th August 2015) - Atkinson, Beth; Bailey, Sallie; Vaughan, Ian P.; Memmott, Jane
Summary: Testing restoration methods is essential for the development of restoration ecology as a science. It is also important to monitor a range of taxa, not just plants which have been the traditional focus of restoration ecology. Here, we compare the effects on ground flora and leaf‐miners, of two restoration practices used when restoring conifer plantations. Two methods of restoration were investigated: clearfelling of plantations and the gradual thinning of conifers over time. Unrestored plantations and native broadleaved woodlands were also surveyed, these representing the starting point of restoration and the reference community, respectively. The study sites consist of two forest types (acidic Quercus woodland and mesotrophic Fraxinus woodland) enabling us to compare the two restoration methods in different habitat types. We use a well‐replicated, large‐scale study system consisting of 32 woodland plots, each 2 ha in size. There were 179 plant species identified in the plots. Clearfelled plots had greater overall ground flora species richness than other management regimes (thinned, unrestored plantation and native woodland), but the richness of woodland plant species did not differ between clearfelled, thinned, native woodland and unrestored plantation plots. More than 10 000 leaf‐miners comprising 122 species were collected. Increased plant species richness was associated with increased leaf‐miner species richness under all management regimes except clearfelled plots. Forest type did not affect the response to restoration method; that is, there was no interaction between management regime and forest type for any of the variables measured. Synthesis and applications . Our results suggest that both the clearfelling and gradual thinning approaches to plantation restoration maintain woodland ground flora species. Either method can be used without detriment to woodland ground flora species richness. However, these methods differed in their effects on the leaf‐miner–plant species richness relationship. If increasing invertebrate herbivore species richness is a concern, the gradual thinning approach is more appropriate. Abstract : Our results suggest that both the clearfelling and gradual thinning approaches to plantation restoration maintain woodland ground flora species. Either method can be used without detriment to woodland ground flora species richness. However, these methods differed in their effects on the leaf‐miner–plant species richness relationship. If increasing invertebrate herbivore species richness is a concern, the gradual thinning approach is more appropriate.